Association of a multiplex immune marker panel with incident cognitive impairment and dementia: The Northern Manhattan Study - Mohammad Abdurrehman Sheikh; Michelle P. Moon; Clinton B. Wright; Jose Gutierrez; Minghua Liu; Tatjana Rundek; Ken Cheung; Mady Hornig; Mitchell S.V. Elkind (Brain, Behavior, & Immunity - Health)
Objective: To determine whether a panel of immune markers adds significant information to known correlates of risk of dementia and cognitive impairment. Background: The impact of immune mechanisms on dementia risk is incompletely characterized. Design/methods: A subsample of the Northern Manhattan Study, a prospective cohort study in the racially/ethnically diverse population of New York City, underwent comprehensive neuropsychological testing up to three times, at approximately 5-year intervals. Cognitive outcomes were adjudicated as no cognitive impairment, mild cognitive impairment (MCI), or dementia. Immune markers were assessed using a multiplex immunoassay on plasma samples collected at the time of the first neuropsychological test. Least absolute shrinkage and selection operator (LASSO) techniques were employed to yield a panel of immune markers linearly related to the outcome of dementia/MCI vs. no cognitive impairment. Nested logistic regression models were run to determine the independent association of the immune marker panel with dementia/MCI after adjusting for other predictors of risk. Results: Among 1179 participants (mean age 70.0 ± 8.9 years, 60% women, 68% Hispanic), immune markers improved model fit above demographic and vascular risk factors (p-value for likelihood ratio test <0.0001) as correlates of MCI/dementia. Individual immune markers found to be associated with dementia/MCI were C-X-C Motif Chemokine Ligand 9 (CXCL9) and C-C Motif Chemokine Ligand 2 (CCL2). The effect of the immune markers was comparable to traditional risk factors, with CCL2 (per SD) having almost the same effect as 1 year of aging and CXCL9 (per SD) showing approximately twice this magnitude. Conclusion: Immune markers are associated with cognitive decline and dementia outcomes in a multi-ethnic cohort. More work is needed to further characterize these associations and determine therapeutic strategies. (Funded by the National Institute of Health/National Institute of Neurological Disorders and Stroke; grant number R01 29993 (Sacco/Elkind)).